Anti-Autophagy Mechanism of Zhi Gan Prescription Based on Network Pharmacology in Nonalcoholic Steatohepatitis Rats - Qin, Chufeng; Luo, Lichuan; Cui, Yusheng; Jiang, Li; Li, Beilei; Lou, Yijie; Weng, Zhuofan; Lou, Jingwen; Liu, Chenxin; Weng, Cuiting; Wang, Zhaojun; Ji, Yunxi (Frontiers in Pharmacology, 2021)
Background & Aims: Zhi Gan prescription (ZGP) has been clinically proven to exert a favorable therapeutic effect on nonalcoholic steatohepatitis (NASH). This study aimed to explore the underlying molecular mechanisms of ZGP action in NASH. Methods: Systematic network pharmacology was used to identify bioactive components, potential targets, and the underlying mechanism of ZGP action in NASH. High fat (HF)-induced NASH model rats were used to assess the effect of ZGP against NASH, and to verify the possible molecular mechanisms as predicted by network pharmacology. Results: A total of 138 active components and 366 potential targets were obtained in ZGP. In addition, 823 targets of NASH were also screened. In vivo experiments showed that ZGP significantly improved the symptoms in HF-induced NASH rats. qRT-PCR and western blot analyses showed that ZGP could regulate the hub genes, PTEN, IL-6 and TNF in NASH model rats. In addition, ZGP suppressed mitochondrial autophagy through mitochondrial fusion and fission via the PINK/Parkin pathway. Conclusions: ZGP exerts its effects on NASH through mitochondrial autophagy. These findings provide novel insights into the mechanisms underlying the effects of ZGP in NASH.